Optimizing Nitrogen Fixation in Vicia sativa: The Role of Host Genetic Diversity - María Isabel López-Román; Cristina Castaño-Herrero; Lucía De la Rosa; Elena Ramírez-Parra (Agronomy)
Common vetch (Vicia sativa L.) is a legume widely used both as a grain and as forage due to its high protein content, which provides considerable nutritional enrichment for livestock feed. As a cover crop, it has the potential to fix atmospheric nitrogen through symbiosis with rhizobia, contributing to sustainable agricultural systems by enhancing soil fertility and reducing the dependence on chemical fertilizers. Although much research has been focused on optimizing Rhizobium inoculants to enhance biological nitrogen fixation (BNF) in leguminous crops, the role of host plant genetic diversity in BNF has been underexplored. This study analyses a collection of V. sativa genotypes to evaluate their BNF by assaying their nodulation capacity, nodule nitrogenase activity, nitrogen fixation potential, and impact on biomass development. Our results reveal large variability in these parameters among the different genotypes, emphasizing the relevance of host legume diversity in the Rhizobium symbiosis. These findings show a direct relationship between nodule biomass development, nitrogen fixation capacity, shoot biomass production, and nitrogen content. However, no correlation was observed for other parameters such as the number of nodules, nitrogenase activity, and shoot nitrogen content. Taken together, these results suggest that selecting genotypes with high BNF capacity could be a promising strategy to improve nitrogen fixation in legume-based agricultural systems.